Soil Characteristics and Irrigation Water Hazards - Jain, B L (Annals of Arid Zone, 2016)
Suitability of irrigation waters in relation to the content of fine mechanical fractions, hydraulic conductivity and cation exchange capacity was evaluated in a highly saline sodic ground water zone in the arid region of south west Rajasthan. Salinity hazards of water increased with increase in the content of silt and clay and was predominant in the surface soil layers. Sodic hazards were lowered with increase in silt and clay content, hydraulic conductivity and cation exchange capacity of the soils.